Adipocyte Fatty Acid-Binding Protein, Cardiovascular Diseases and Mortality - Lee, Chi-Ho; Lui, David T. W.; Lam, Karen S. L. (Frontiers in Immunology, 2021)
It has been increasingly recognized that inflammation plays an important role in the pathogenesis of cardiovascular disease (CVD). In obesity, adipose tissue inflammation, especially in the visceral fat depots, contributes to systemic inflammation and promotes the development of atherosclerosis. Adipocyte fatty acid-binding protein (AFABP), a lipid chaperone abundantly secreted from the adipocytes and macrophages, is one of the key players mediating this adipose-vascular cross-talk, in part via its interaction with c-Jun NH2-terminal kinase (JNK) and activator protein-1 (AP-1) to form a positive feedback loop, and perpetuate inflammatory responses. In mice, selective JNK inactivation in the adipose tissue significantly reduced the expression of AFABP in their adipose tissue, as well as circulating AFABP levels. Importantly, fat transplant experiments showed that adipose-specific JNK inactivation in the visceral fat was sufficient to protect mice with apoE deficiency from atherosclerosis, with the beneficial effects attenuated by the continuous infusion of recombinant AFABP, supporting the role of AFABP as the link between visceral fat inflammation and atherosclerosis. In humans, raised circulating AFABP levels are associated with incident metabolic syndrome, type 2 diabetes and CVD, as well as non-alcoholic steatohepatitis, diabetic nephropathy and adverse renal outcomes, all being conditions closely related to inflammation and enhanced CV mortality. Collectively, these clinical data have provided support to AFABP as an important adipokine linking obesity, inflammation and CVD. This review will discuss recent findings on the role of AFABP in CVD and mortality, the possible underlying mechanisms, and pharmacological inhibition of AFABP as a potential strategy to combat CVD.